2000
DOI: 10.1183/09031936.00.16478100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of exhaled nitric oxide

Abstract: There has been intense research into the role nitric oxide (NO) plays in physiological and pathological mechanisms and its clinical significance in respiratory medicine.Elevated levels of exhaled levels of exhaled NO in asthma and other inflammatory lung diseases lead to many studies examining NO as potential markers of airway inflammation, enabling repeated noninvasive and standardized monitoring of airway inflammation. In airway inflammation, NO is not merely a marker but may have antiinflammatory and pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 76 publications
6
135
1
11
Order By: Relevance
“…Inclusion criteria were being healthy and 20-50 yrs of age. To decrease the likelihood of subclinical airways disease, exclusion criteria were: current respiratory symptoms; history of respiratory disease; ex-smokers with a smoking history of .10 pack-yrs or who had smoked in the last year; cardiac or neurological comorbidity; structural abnormalities of the chest wall; and an exhaled nitric oxide concentration of .35 ppb [15] or a positive methacholine challenge [16]. The study was approved by the Lower South Ethics Committee (Dunedin, New Zealand) and all participants gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were being healthy and 20-50 yrs of age. To decrease the likelihood of subclinical airways disease, exclusion criteria were: current respiratory symptoms; history of respiratory disease; ex-smokers with a smoking history of .10 pack-yrs or who had smoked in the last year; cardiac or neurological comorbidity; structural abnormalities of the chest wall; and an exhaled nitric oxide concentration of .35 ppb [15] or a positive methacholine challenge [16]. The study was approved by the Lower South Ethics Committee (Dunedin, New Zealand) and all participants gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis revealed that asthmatic trawler workers had substantially higher FE NO levels compared to asthmatic salmon workers (males). Fractional exhaled nitric oxide is thought to reflect eosinophilic inflammation [33][34][35] and behaves as a biomarker of ''allergic asthma'' phenotype rather than asthma itself. The higher FE NO levels in trawler workers could accordingly point to a greater influence of allergic mechanisms among these workers.…”
Section: Discussionmentioning
confidence: 99%
“…Plants utilise NO as a multifarious signal molecule in growth and differentiation processes [6][7][8]. Concentration measurement of exhaled NO is a well-established procedure for monitoring inflammatory diseases such as asthma [9,10]. Commercial detection devices achieve detection limits of about 1 parts per billion (ppb), but are not able to differentiate between isotopologues.…”
Section: Introductionmentioning
confidence: 99%